Consumer and business credit management - Cole, Robert; Mishler, Lon (Boston, Mass. : Irwin/McGraw-Hill, 1998)
Business
Keywords: Credit management; Business credit; Consumer credit; Retail management; Cash loan credit; Real estate credit; Interantional trade credit